Elaboración del estudio de prefactibilidad para el montaje de un laboratorio de productos cosméticos para el grupo empresarial Lozano & Asociados (2015)
This Labor Grade performs prefeasibility study for the assembly of a cosmetics laboratory in the city of Bogota. This develops addressing the need for autonomy that Lozano & Asociados business group has in providing inventory hair products in which it conducts its business. The Lozano & Asociados business group has an experience of over 20 years in the cosmetics sector in service delivery and marketing of cosmetic products. The need is evident is that the company may be autonomous in the manufacture of products for immediate sale in its current niche. Thus Degree Work "Development of feasibility study for the installation of a laboratory of cosmetic products Lozano & Asociados business group", comprising the steps of: i) a description of the current profile of the project, ii) identification and alignment Strategic Project (IAEP), and iii) formulation and evaluation studies. With the foregoing it is looking to argue the viability of the project through the development of each of the stages mentioned.